Innovation in Ornamental Plant Care Systems Based on the Internet of Things (IoT) Using Arduino Leonardo - Supriyanto, Supriyanto; Widiana, Siska Ayu (Sebatik, 2025)
Anthurium ornamental plants are known for their high aesthetic and economic value, requiring optimal care, particularly in terms of watering, temperature, and soil moisture. However, in practice, the watering process is still mostly done manually and often fails to meet the actual needs of the plants, potentially causing damage or even plant death. Flower Shop "Cemara Indah" in Semarang, a business specializing in ornamental plants, faces similar challenges, especially in the care of Anthurium plants. Therefore, this study aims to design and implement an automatic plant care system based on Arduino Leonardo, utilizing a soil moisture sensor and a DHT11 sensor to monitor temperature and humidity. The system reads soil and environmental conditions and regulates watering according to the appropriate moisture and temperature levels required by the plants. Sensor readings are displayed on an LCD and can be accessed via a local network using an Ethernet Shield. The results of this system design are expected to improve efficiency in terms of time, labor, and cost in plant care, while sustainably maintaining the quality and health of Anthurium plants. This system also offers an innovative solution for ornamental plant enthusiasts to care for their plants in a more modern and controlled manner.